Evaluation of carotid artery elasticity and its influencing factors in non-obese PCOS patients using a technique for quantitative vascular elasticity measurement - Hu, Yanli; Chen, Bo; Pan, Yingzheng; Xing, Kewei; Xiao, Zhibo; Sheng, Bo; Li, Jia; Dong, Hongmei; Lv, Furong (Frontiers in Endocrinology, 2024)
Objectives: To evaluate the intima-media thickness (IMT) and elasticity of the carotid artery in non-obese polycystic ovary syndrome (PCOS) patients using a quantitative technique for vascular elasticity measurement and to explore the influencing factors.Methods: Sixty patients diagnosed with non-obese PCOS without metabolic and cardiovascular diseases from January to December 2022 were prospectively selected (case group), and 60 healthy volunteers matched for body mass index were included as the control group. Body weight, height, heart rate, blood pressure, and waist-to-hip ratio were recorded. Fasting blood samples were drawn to measure hormone levels including total testosterone (TT), sex hormone-binding globulin (SHBG), fasting plasma glucose (FPG), fasting insulin (FINS), lipids, and homocysteine (Hcy). The insulin resistance index (HOMA-IR) and free androgen index (FAI) were calculated. Ultrasound elastography was used to measure the IMT and elastic function parameters of the right carotid artery, including vessel diameter, wall displacement, stiffness coefficient, and pulse wave velocity. Differences in various parameters between the two groups were analyzed, and correlations between the carotid stiffness coefficient and other serological indicators were assessed using Spearman correlation analysis.Results: the waist-to-hip ratio (WHR) was higher in the case group than in the control group (P<0.05).The hormone level serological indicators TT and FAI were higher in the case group than in the control group, and SHBG was lower (all P<0.05). The metabolism-related serum indicators LDL-C, HDL-C, FPG, TC and TG levels were not statistically different between the two groups (all P>0.05), and serum FINS, HOMA-IR, and Hcy levels were significantly higher in the case group than in the control group (all P<0.05).The carotid artery displacement in the case group was significantly smaller than that in the control group (P<0.05), and carotid IMT, hardness coefficient, and pulse wave propagation velocity were greater in the case group than in the control group (all P<0.05). The carotid elastic stiffness coefficient was positively correlated with WHR, TT, SHBG, FAI, FINS, HOMA-IR and Hcy to varying extents and negatively correlated with SHBG.Conclusion:In non-obese PCOS patients with no metabolic or cardiovascular disease, the carotid stiffness coefficient was increased and correlated with indicators of hyperandrogenism, insulin resistance, and hyperhomocysteinemia.